Risk of infections in patients with NAFLD and Type 2 Diabetes under treatment with SGLT2 inhibitors and relationship with liver outcomes: A retrospective case-control study - Bañares, Juan; Manzano-Nuñez, Ramiro; Prió, Alba; Rivera-Esteban, Jesús; Camps-Relats, Laura; Villarejo, Ana; Ruiz-Ortega, Lourdes; Pons, Mònica; Ciudin, Andreea; Salcedo, María Teresa; Vargas, Víctor; Genescà, Joan; et al. (Frontiers in Endocrinology, 2022)
Introduction Non-alcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disease in developed countries, with its incidence growing parallel to the epidemics of obesity and type 2 diabetes mellitus (T2DM). Sodium-glucose co-transporter-2 inhibitors (SGLT2i) are becoming a cornerstone in the management of cardiovascular health and some studies suggest the potential role in NAFLD. However, patients under treatment with SGLT2i are at risk of developing genitourinary fungal infections (GFIs). Moreover, both NAFLD and SGLT2i have a strong influence on the immune system, and therefore the risk of infections other than GFIs could be increased in NAFLD patients treated with SGLT2i. We aimed to examine the possible association of SGLT2i with infections and hepatic outcomes in NAFLD patients. Methods We conducted a case-control study including NAFLD patients with T2DM visited at the Liver Unit outpatient clinic from 2016 to 2021 with a minimum follow-up of 6 months by selecting 65 patients receiving SGLT2i and 130 matched patients with other types of antidiabetic treatment. Results During follow-up, GFIs were significantly higher in the SGLT2i group (15.4% vs. 3.8%; p=0.008), whereas there were no differences in the occurrence of overall infections (41.5% vs. 30%; p=0.1) nor in other types of specific infections. In the multivariable analysis, treatment with SGLT2i was not independently associated with higher odds of overall infection. On the other hand, SGLT2i patients showed a significantly lower incidence of hepatic events (1.5% vs. 10.7%; p=0.02). There were no significant different in all-cause mortality between cases and controls. Conclusions NAFLD patients with T2DM receiving SGLT2i more frequently presented GFIs, whereas the incidence of other types of infections was not found to be higher than in other patients with NAFLD and T2DM treated with other drugs. Moreover, SGLT2i-treated patients had a lower occurrence of hepatic events. Further studies are warranted to validate our data.